The Human Concept in Qur’anic Education Based on Tafsir Tarbawi Study of Q.S. Al-‘Alaq 1–5 and Its Educational Implications - Kallabe, Nur 'Azizah; Abdurrazzaq; Kristina Imron (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore and analyze the concept of human beings in Qur’anic education based on a tafsir tarbawi analysis of Q.S. Al-Alaq verses 1 to 5 and to formulate its educational implications for contemporary Islamic education. The research employs a qualitative design using a literature review approach. The primary data source is the Qur’an, specifically Surah Al-Alaq 1 to 5, supported by classical and contemporary tafsir tarbawi interpretations. Secondary data consist of scholarly books, peer-reviewed journal articles, and relevant academic studies related to Islamic education and the human concept in the Qur’an. Data were collected through documentation techniques and analyzed using qualitative content analysis to identify key themes, meanings, and educational values contained in the verses. The findings of this study reveal that the Qur’an conceptualizes human beings as learning creatures endowed with intellectual, spiritual, and moral potentials. The command iqra in Surah Al-Alaq emphasizes that education in Islam is a holistic process that integrates intellectual development, character formation, and spiritual awareness. Humans are portrayed as servants of Allah and as khalifah on earth who are responsible for continuously seeking knowledge and implementing divine values in real life. The study concludes that Islamic education must be grounded in the integration of revelation and reason, resulting in an educational paradigm that is spiritually oriented, intellectually dynamic, and morally transformative. These findings provide theoretical contributions to Islamic educational philosophy and practical implications for the development of curricula and learning models based on Qur’anic values.